HUBUNGAN SELF ASSESSMENT TERHADAP MOTIVASI BELAJAR BAHASA ARAB SISWI SD TAHFIZH AT-TAMAM PUTERI - Stevi Andriani; Muhammad Azhar; Adilah Salsabila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the relationship between self-assessment and Arabic language learning motivation among fifth-grade students at SD Tahfizh At-tamam Puteri, Pekanbaru, Indonesia. Low motivation in Arabic learning has become a critical issue in Islamic elementary schools. Self-assessment is proposed as a strategic approach to empower students to evaluate their learning progress and enhance intrinsic motivation. A quantitative method with a correlational survey design was employed. The sample consisted of 25 students selected through purposive sampling. Data were collected using closed-ended Likert-scale questionnaires measuring self-assessment and Arabic learning motivation. Analysis utilized Pearson correlation and simple linear regression, preceded by normality (Shapiro-Wilk), linearity, and homogeneity (Levene) prerequisite tests. Results showed that both variables were normally distributed (X: W = 0.922, p = 0.059; Y: W = 0.954, p = 0.309), the relationship was linear (F = 18.62, p = 0.0003), and variances were homogeneous. Pearson correlation yielded r = 0.669 with R² = 0.447, indicating a strong positive correlation (p = 0.0003). Self-assessment explained 44.74% of variance in Arabic learning motivation. The regression equation Ŷ = 28.25 + 0.617X confirms that each 1-point increase in self-assessment raises motivation by 0.617 points.